(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The present study is devoted to a comparative analysis of two tactical and technical approaches to laparoscopic sleeve resection of the stomach in patients with morbid obesity: the classical technique (Classic) and a modified version with enhanced restriction (Hard). The study included 785 patients operated on from 2019 to 2022, with follow-up for at least 36 months. Early and late surgical and metabolic complications, body weight dynamics, and the frequency of repeated weight gain were evaluated.